Students’ non-cognitive skills in times of crisis: COVID-19 in Mexico - Tonatiuh Cruz Herrera; Manuel Lara González; Alejandro López-Feldman (Social Sciences and Humanities Open, 2023)
The COVID-19 pandemic caused serious disruptions in the school systems throughout the world. In this work we look at the effect that the pandemic had in non-cognitive skills of students in Mexico. Few studies have looked at this relationship and the studies available have looked at the effects on children in high-income countries. Our results show that growth mindset declined, while social awareness and self-management improved during the pandemic. The negative effects on growth mindset are certainly a reason for concern, while the improvement on the other measures can be seen as a silver lining amidst the chaos created by the pandemic.